Az afrikai sertéspestis (ASP) terjedése és a járvány kezelésének módja Ukrajnában - Agij Vasyl (2019)
As a bitter experience, every European hunter and farmer has learned that African swine fever is a serious threat to both domestic swine and wild boar. The disease is caused by a virus and the infection is almost always fatal. The proliferation of viruses within the host is very slow, but the outbreak of the infection can lead to over 80 percent lethality. The infection is clearly spread with blood, blood-rich tissues, pork products that have not been exposed to heat and body fluids. Fortunately, ASF cannot cause human disease. The contact with the infected swine or its meat, but even the consumption of ASP infected pork does not pose a health risk. Nonetheless, African Swine Fever can cause huge economic losses, destroying swine vertices in entire regions, causing huge economic damage. As the vaccine against ASP still does not exist, the only way to protect against it is to keep animal health rules up to date, as effective as possible isolation of pig farms and the increased control of wild boar stock. In addition, an important defense procedure is to provide the general public with as much information as possible about the destruction of infected individuals and ways to monitor and occasionally ban the transportation of pork and meat products that have not been exposed to heat.